Performance Comparison Of Steam And Air-Steam Gasification Reactor - Munisuaran, Kishen (Universiti Sains Malaysia, 2022)
Renewable energy sources are being used more frequently as a result of rising energy demand and environmental concerns. A growing source of sustainable energy is biomass. Thermochemical and biological processes are the most common for turning biomass to energy. When a gasifying agent is used, the solid fuel is converted into the gaseous fuel known as PG by a thermochemical process called gasification. High hydrogen production cannot be attained when air is used as the gasifying agent. To solve this issue, a gasifying agent will be used because steam can improve hydrogen production. A self-sustained steam biomass gasifier was modified and fabricated to enable proper and fully supply of steam to the reactions. Thus, the use of steam alone and steam incorporated with air as gasification agents was explored in this research. Steam was generated using an electric steam boiler. The gasifier performance and gasification processes were characterized based on various parameters such as gasifier outlet and grate temperature, steam flow rate, steam-to-biomass ratio, heating values and producer gas composition at the top. The steam flow rates used are in the range of 11.24 to 40 ml/min for steam gasification of wood pellets and optimum steam flow rate is used for steam gasification of different biomass fuels and air-steam gasification of wood pellets. As for the gasifier characterization, the highest temperature recorded at the grate was 545 ºC and 510 ° C at the outlet for steam gasification of wood pellets. The optimum S/B ratio for producing the desired gas quality and compositions was found to be 1.9 having the highest HHV of 15.1 MJ/Nm³ in steam gasification of wood pellets. In steam gasification of different biomass fuels, wood pellets were found to yield the highest hydrogen and methane concentrations and HHV followed by PKS. As for air-steam gasification, the highest temperature recorded at the grate was 975 ºC and 905 ° C at the outlet. In this study, the optimum S/B ratio for producing the desired gas quality and compositions was found to be 1.7 at air flow rate of 50 LPM and optimum steam flow rate having the highest HHV of 5.27 MJ/Nm³.